Application of Artificial Intelligence in Healthcare - Tavares, Jorge (2024)
Tavares, J. (2024). Application of Artificial Intelligence in Healthcare: The Need for More Interpretable Artificial Intelligence. Acta Medica Portuguesa, 37(6), 411-414. https://doi.org/10.20344/amp.20469